Work-related episodic memories can increase or decrease motivation and psychological health at work. Issue 4 (2nd October 2019) - Philippe, Frederick L.; Lopes, Maxime; Houlfort, Nathalie; Fernet, Claude
ABSTRACT: Research on the psychological mechanisms underlying employee motivation and psychological health at work has been limited to general and chronic workplace factors, such as job strenuousness or management style. In two studies, we examine how unique and time-specific work life events encoded as episodic memories can influence employee motivation and psychological health at work as a function of how these events are recalled having been experienced in terms of need satisfaction. In Study 1, participants described a self-defining work-related memory and rated it for need satisfaction. They also completed scales of need satisfaction at work, self-determined motivation, and positive and negative indicators of psychological health (i.e. work satisfaction and burnout). In Study 2, participants completed the same tasks and scales, but they did it again two years later. Results revealed that need satisfaction in self-defining work-related memories was associated with self-determined motivation and indicators of psychological health at work, over and above demographics (age, sex, weekly hours worked, education) and general perceptions of need satisfaction at work. Moreover, it predicted increases in self-determined motivation and in work satisfaction and decreases in burnout over two years. The present findings underscore the importance of considering unique work life events encoded in memory.